Full-field characterisation of the stress concentration of blocked twins by high-resolution EBSD in alpha-uranium - Earp, P; Barhli, S; Marrow, T (International Congress on Fracture, 2017)
A novel method has been applied to quantify the stress concentration at blocked twins, via a formulation of the J-integral, using the elastic strain field data obtained by High-Resolution Electron Backscatter Diffraction. It has been applied here to twins in a coarse-grained anisotropic metal, alpha-uranium. This method has applications to slip bands and short cracks, and can aid the quantification of stress concentrating features that may nucleate brittle fracture.